Inhibition of PTP1B Promotes M2 Polarization via MicroRNA-26a/MKP1 Signaling Pathway in Murine Macrophages - Xu, Xiaolong; Wang, Xuerui; Guo, Yuhong; Bai, Yunjing; He, Shasha; Wang, Ning; Lin, Yan; Fisher, Marc; Liu, Qingquan; Yao, Yongming (Frontiers in Immunology, 2019)
Sepsis is a life-threatening condition that often occurs in the intensive care unit. The excessive activation of the host's immune system at early stages contributes to multiple organ damage. Mitogen-activated protein kinase phosphatase-1 (MKP1) exerts an important effect on the inflammatory process. In our recent bioinformatic analysis, we confirmed that the inhibition of protein tyrosine phosphatase-1B (PTP1B) significantly promoted the expression of MKP1 in murine macrophages. However, the underlying mechanism and its effect on macrophage polarization remain unclear. In this study, we show that the suppression of PTP1B induced upregulation of MKP1 in M1 macrophages. A RayBiotech mouse inflammation antibody assay further revealed that MKP1-knockdown promoted pro-inflammatory cytokine (IL-1β, IL12p70, IL-17, IL-21, IL-23, and TNF-α) secretion but suppressed anti-proinflammatory cytokine (IL-10) production in M2 macrophages. Phospho-proteomics analysis further identified ERK1/2 and p38 as downstream molecules of MKP1. Moreover, we found that the inhibition of PTP1B lowered the expression of miR-26a, showing a negative correlation with MKP1 protein expression. Thus, we concluded that the inhibition of PTP1B contributes to M2 macrophage polarization via reducing mir-26a and afterwards enhancing MKP1 expression in murine macrophages.